Pengaruh Kualitas Pelayanan Kefarmasian Terhadap Tingkat Kepuasan Pasien Di Empat Apotek Kota Tangerang Selatan - Melizsa Melizsa; Renato Putra Herwina; Magdalena Niken (STIKes Kharisma Persada, 2020)
There has been a shift in the orientation of pharmaceutical services from only drug management to comprehensive patient care (Pharmaceutical Care). Some factors that influence the level of patient satisfaction are the quality of pharmaceutical services. The purpose of this study was to determine the Effect of Pharmaceutical Service Quality on Patient Satisfaction Level in Four Pharmacy City of South Tangerang. This research is a type of quantitative analytic research with cross sectional method. This study uses an accidental sampling method by distributing questionnaires to 100 respondents in four South Tangerang city pharmacies. The results showed that the quality of pharmaceutical services has a strong influence on the level of patient satisfaction that has a Pearson correlation of 0.714. The assessment category for the service quality variable produced a pretty good answer (65%) and quite satisfied (75%) forpatient satisfaction. The quality of services provided by the four pharmacies is good, but it must be continuously improved so that there is no decrease in patient satisfaction in the future.